EFEKTIVITAS KEBIJAKAN DANA DESA TERHADAP PEMBERDAYAAN MASYARAKAT DAN PEMBANGUNAN INFRASTRUKTUR DI DESA MAGGENRANG - Lilis, Lilis; Akhmad, Akhmad; Jaya, Asri (Jurnal Ekonomi Sakti, 2025)
Village Funds are funds sourced from the State Budget transferred through the district and city budgets used to finance the implementation of government, implementation of development, and community development. Based on Law No. 6 of 2014, village development management begins with planning, implementation, and supervision. This study aims to analyze the effectiveness of the Village Fund policy on community empowerment and infrastructure development in Maggenrang Village, Kahu District, Bone Regency. Using qualitative methods through observation and interviews, the results of the study indicate that the use of village funds is still not optimal. Community empowerment is still focused on the agricultural sector through the formation of farmer groups and the distribution of rice seeds, while other sectors such as skills training and small business development have not been developed much. In terms of infrastructure, the construction of roads, embankments, and irrigation channels has provided real benefits for mobility, agriculture, and citizen security, although equitable development and fulfillment of socio-spiritual needs have not been fully achieved. The effectiveness of the use of village funds in Maggenrang Village requires a balance between physical development and community empowerment programs so that development results are more sustainable and equitable. Keywords: Effectiveness, Village Funds, Community Empowerment, Infrastructure Development, Maggenrang Village.